Surface modification via silver nanoparticles attachment: An ex-situ approach for enhancing the electron field emission properties of CNT field emitters. (2021) - Moeen Hasan Raza, Mohammad; Sadiq, Mohd; Khan, Sunny; Sarvar, Mohd; Parveen, Shama; Masheerul Aalam, Shah; Zulfequar, Mohammad; Husain, Samina; Ali, Javid
Abstract: A novel one-dimensional carbon material Known as carbon nanotubes (CNTs), having their high aspects ratio and as well as advance electrical properties which make them best candidate for cathode field emitters. In this work, we have introduced the easy and cost-effective approach to improving the CNT field emitters emission properties. Here we have modified the surface of CNT field emitter via decorating with silver nanoparticles (Ag NPs). Attachment of Ag NPs on CNT surface via thermal evaporation technique. The as-prepared samples of pristine CNTs and decorated CNTs with Ag NPs were characterized by the scanning electron microscope for morphology analysis, quality and qualitative analysis done by Raman spectroscopy. Here we have applied the Fowler Nordheim hypothesis for the analysis of electron field emission of as-prepared cathode field emitters. The turn-on ( E to ) and threshold ( E th ) field reduced after CNT field emitters coated with Ag NPs. The field enhancement factor ( β ) and emission current density ( J ) enhanced after coating. Ag NPs decorated/coated CNT field emitters can be utilized in field emission device applications.